Management of the Emergent Literacy Program for Early Childhood at the Birrul Walidain Learning House - Novan Ardy Wiyani; Zalik Nuryana (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
Early literacy is now an essential need in early childhood. Children must have initial reading and writing skills to be ready to enter the elementary school level. This study aimed to describe and analyze four management activities of an emergent literacy program in early childhood. This study is qualitative research classified as phenomenological research. The subjects of this study consisted of the managers, teachers, parents, and students of the Birrul Walidain learning house. This study applied interviews, observation, and documentation to collect the data. Then the data were analyzed using the data analysis techniques of the Miles and Huberman models, including data reduction, data presentation, and verification. The findings showed that the four management activities of the emergent literacy program in early childhood at the Birrul Walidain learning house are as follows: (1)planning the emergent literacy program; (2) organizing the emergent literacy program; (3) implementing an emergent literacy program by organizing initial reading and writing learning activities according to a predetermined schedule; (4) controlling the emergent literacy program. The results of this study had implications for the reconceptualization of emergent literacy programs in early childhood in terms of four managerial activities: planning, organizing, implementing, and controlling.